1999
DOI: 10.1063/1.479585
|View full text |Cite
|
Sign up to set email alerts
|

Two-pulse laser control for selective photofragment orientation

Abstract: The nuclear wave packet dynamics in the potential well of a bound molecule can be controlled by an intense infrared ͑IR͒-laser pulse. The phase of the nuclear wave packet motion is shown to depend on the phase of the laser field and the initial orientation of the molecule. We demonstrate, for diatomic heteronuclear molecules, that these spatial effects can be used to control the angular distribution of photofragments by selective dissociation of molecules with a given initial orientation from a sample of rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…The resonant case was discussed in detail in Ref. 8, and we found that molecules with opposite orientations will oscillate out of phase, as seen in Fig. 2͑b͒.…”
Section: Orientation Dependence In Off-resonant Forced Wp Motionmentioning
confidence: 75%
See 4 more Smart Citations
“…The resonant case was discussed in detail in Ref. 8, and we found that molecules with opposite orientations will oscillate out of phase, as seen in Fig. 2͑b͒.…”
Section: Orientation Dependence In Off-resonant Forced Wp Motionmentioning
confidence: 75%
“…In the resonant case discussed in Ref. 8, we showed perfect agreement between the 1D and 3D model, and interpreted this as the absence of coupling between the rotational and vibrational motion, allowing us to represent the full 3D simulations as a sum over of independent 1D simulations. The resonant field only makes very small changes to the angular distribution, even if the intensity is increased to the same value as the off-resonant field, Iϭ10 12 W/cm 2 .…”
Section: Orientation Dependence In Off-resonant Forced Wp Motionmentioning
confidence: 88%
See 3 more Smart Citations